RuvB-Like Protein 2 Interacts with the NS1 Protein of Influenza A Virus and Affects Apoptosis That Is Counterbalanced by Type I Interferons - Yimeng Wang; Jianhong Zhou; Samuel G. Mackintosh; Yuchun Du (Viruses, 2021)
The NS1 protein of influenza A virus (IAV) plays important roles in viral pathogenesis and host immune response. Through a proteomic approach, we have identified RuvB-like proteins 1 and 2 (RuvBL1 and RuvBL2) as interacting partners of the NS1 protein of IAVs. Infection of human lung A549 cells with A/PR/8/34 (PR8) virus resulted in reductions in the protein levels of RuvBL2 but not RuvBL1. Further studies with RuvBL2 demonstrated that the NS1-RuvBL2 interaction is RNA-independent, and RuvBL2 binds the RNA-binding domain of the NS1. Infection of interferon (IFN)-deficient Vero cells with wild-type or delNS1 PR8 virus reduced RuvBL2 protein levels and induced apoptosis; delNS1 virus caused more reductions in RuvBL2 protein levels and induced more apoptosis than did wild-type virus. Knockdown of RuvBL2 by siRNAs induced apoptosis and overexpression of RuvBL2 resulted in increased resistance to infection-induced apoptosis in Vero cells. These results suggest that a non-NS1 viral element or elements induce apoptosis by suppressing RuvBL2 protein levels, and the NS1 inhibits the non-NS1 viral element-induced apoptosis by maintaining RuvBL2 abundance in infected cells in the absence of IFN influence. In contrast to Vero cells, infection of IFN-competent A549 cells with PR8 virus caused reductions in RuvBL2 protein levels but did not induce apoptosis. Concomitantly, pretreatment of Vero cells with a recombinant IFN resulted in resistance to infection-induced apoptosis. These results demonstrate that the infection-induced, RuvBL2-regulated apoptosis in infected cells is counterbalanced by IFN survival signals. Our results reveal a novel mechanism underlying the infection-induced apoptosis that can be modulated by the NS1 and type I IFN signaling in IAV-infected cells.